OCCURRENCE AND DISTRIBUTION OF SOME POTATO DISEASES AFTER WINTER STORAGE PERIOD - Manuela Hermeziu; Lorena Adam; Diana Petre (Agricultura)
The paper aimed to present the evolution of twelve Romanian potato varieties (Cezarina, Marvis, Sarmis, Castrum, Ervant, Asinaria, Brașovia, Azaria, Darilena, Foresta, Christian) under the aspect of diseases developed after a period of storage.the experience took place in the years 2021-2022 to the National Institute for Research and Development for Potato and Sugar Beet Brasov. Incidence of some tuber diseases like, dry rot, silver scurf, common scab and black scurf were monitored. Considering the results, Brasovia variety is very sensitive to common scab (15.13%) but resistant to silver scurf (2.25%), meanwhile Christian variety is resistant to common scab (3%) and does not show any resistance to silver scurf (64,38%). To dry rot the most sensitive turned out to be the Asinaria variety (5.88%) and the least sensitive was the Sevastia variety (1.88%).